1991
DOI: 10.1177/002246699102400408
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Decisions To Transfer From Special To General Education

Abstract: primary reasons cited for leaving special education suggest that teachers transfer from special to general education because of administrative factors and the stress involved in working with special education students. Implications for educational agencies are addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
167
0
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(180 citation statements)
references
References 17 publications
9
167
0
4
Order By: Relevance
“…This finding adds to previous research related to satisfaction in the work place as a motivator for retention (Billingsley & Cross, 1991;Gersten et al, 2001). This study should promote educational researchers to further the research related to this area.…”
Section: The Value Placed On Induction Support and Intent To Remain Isupporting
confidence: 77%
See 3 more Smart Citations
“…This finding adds to previous research related to satisfaction in the work place as a motivator for retention (Billingsley & Cross, 1991;Gersten et al, 2001). This study should promote educational researchers to further the research related to this area.…”
Section: The Value Placed On Induction Support and Intent To Remain Isupporting
confidence: 77%
“…Much of the research in special education attrition shows that a lack of administrative support is the underlying reason for teachers leaving special education (Billingsley & Cross, 1991;Edgar & Pair, 2005;Kaff, 2004). Special education teachers report many of the same reasons for burnout as their general education peers Miller, Brownell, & Smith, 1999).…”
Section: Factors Contributing To Special Educator Attritionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is discussed the implications of these findings for programs aimed at preventing teacher burnout 9 .To improve educational services to students with disabilities, Buell et al (1999) highlights perceptions of ability to positively affect students, understanding of inclusion, self-efficacy in serving students in inclusive settings, the need for in-service training in various areas, and the availability of supports to promote inclusion were examined for both special and general education teachers 10 .Bonnie et al (1991)explored why some special education teachers choose to stay in teaching, but leave their special education assignments. It also identified deterrents and potential incentives that might lead former special educators to reconsider teaching positions in special education and deduced that teachers transfer from special to general education because of administrative factors and the stress involved in working with special education students 11 . The study of Singh (1996)collected data regarding theplace of working indicated that the teachers who remained in place experienced significantly less stress, and a better working environment than those teachers who left 12 .…”
Section: IImentioning
confidence: 99%